Pumpkinhead ashes to ashes - West, Jake, 1972-; Krevoy, Brad; Kushner, Donald; Spengler, Pierre; Werner, Barbara; Werner, John (Culver City, Calif. : Sony Pictures Home Entertainment, 2007)
The inhabitants of a small town ask the witch Haggis to invoke Pumpkinhead to avenge the desecration of their loved ones after they discover the town's doctor has been selling their organs and dumping the bodies in the swamp
Sequel to the 1989 and 1994 films,'Pumkinhead' and' Pumpkinhead II : blood wings
Title from title screen
Director of photography, Erik Alexander Wilson ; editor, Justin Rogers ; music, Rob Lord
Cast: Lance Henriksen, Lisa McAllister, Tess Panzer, Lynne Verrall, Doug Bradley
DVD Format
In English, French, or Portuguese with optional English, Chinese, French, Japanese, Portuguese, or Spanish subtitles
Keywords: Monsters -- Drama; Revenge -- Drama